Folk and traditional medicine: On the possibility of integrating medical systems, practices and methods in contemporary Tuva - Valentina I. Kharitonova (Novye issledovaniâ Tuvy, 2018)
The article examines how “folk medicine” is practiced in the Republic of Tuva, with a special focus on the current legislation and substatutory acts. For our sources, we rely on the not-too-numerous publications on the rise and functioning of traditional and folk medicine in Tuva, as well as on our field and laboratory materials over a number of years, and media and Internet sources. We start with analyzing the existing classification of various types of medicine - “folk”, “traditional”, “traditional medical system”, etc., emphasizing the specific use of terminology (“complementary” and “alternative” medicine, or “additive” and “alternative” medicine). Also examined are the sources and meaning of the terms “folk healing’, “folk healer” and “practitioner of folk medicine”. Analyzing the federal legislative acts, as well as those of several republics in the region of Siberia, where shamanism is widespread, we trace out some of the practices of integrating various practices of healing and invigoration into the single system of health preservation as recognized by law. Special attention is paid to the situation in the Republic of Tuva and the recent order of the regional Ministry of Healthcare on the use of traditional medicine. Another recent creation in Tuva was the regional Research Institute of Medical and Social Problems and Administration, which has the Department of Traditional Medicine, Social Prevention and Rehabilitation within its structure. Since June 28, 2017, the institute also features a center of folk medicine.